IMPLEMENTASI METODE HABITUASI PERSPEKTIF AL GHAZALI DALAMMEMBENTUK KARAKTER RELIGIUS DI MI NURUSSALAM - Khusnamelda Fairushofiddina Haq; Abu Darda Abu (Joyful Learning Journal, 2026)
Religious character education at the elementary school level currently faces complex contextual challenges, ranging from the erosion of ethical manners (adab) in the social environment to the high intensity of digital distractions that divert children’s spiritual focus. At MI Nurussalam Ngawi, a real challenge can be seen in the inconsistency of students’ religious behavior when they are outside the supervision of the school. The madrasah responds to this phenomenon through the implementation of the habituation method (ta’wīd) based on Al-Ghazali’s theory, which emphasizes the paradigm of Al-Zhahir al-Thahir, namely the arrangement of outward discipline as the main instrument to form inner piety and purify the souls of students. Therefore, this study aims to analyze the implementation of the habituation method according to Al-Ghazali’s perspective at MI Nurussalam Ngawi along with its supporting and inhibiting factors. The type of research used is descriptive qualitative with a field research design. The results of the study show that: (1) the implementation of habituation is carried out through the conditioning of systematic daily physical activities such as welcoming students, congregational prayers, dhikr, and the application of the tsawāb wa ‘iqāb (reward and punishment) instrument. This process describes a transformation in students’ behavior, which initially is at the stage of takalluf (worship performed due to burden or supervision), gradually becoming mudāwamah (routine), until it reaches the stage of malakah, where the awareness of adab emerges spontaneously in daily life; (2) the main supporting factors are the religious culture of the madrasah and teachers’ exemplary behavior (uswah), while the main obstacles include weak synchronization of supervision within the family environment as well as the influence of gadget use which triggers a regression in the consistency of students’ character.